Partisipasi Anggota Kelompok Wanita Tani (Kwt) dalam Mewujudkan Ketahanan Pangan Rumah Tangga di Kecamatan Colomadu Kabupaten Karanganyar - Arien Eka Anggraini Widiastuti (CV. Publikasi Indonesia, 2022)
Food security is one of the national development programs because the availability of food ingredients (energy sources, protein, fat) decreases. Colomadu Subdistrict is one of the sub-districts that supports household food security programs through the use of yard land carried out by the Farmer Women's Group (KWT). The success of this activity can be seen from the participation of KWT members. This research aims to analyze the level of participation of KWT members, factors affecting participation, and the influence of factors affecting participation on the participation of KWT members in realizing household food security. Quantitative methods with survey techniques are the basis of this research method. The determination of the location used as the location of the research was chosen deliberately in the Colomadu subdistrict area.. Proportional random sampling techniques are selected for sample determination. Multiple linear regression analysis was used to analyze the data of this research. The results showed that the participation rate in the planning, implementation, and enjoying results stages was in the very high category, while participation in the evaluation stage was in the high category. Age, level of formal education, level of availability of free time, level of family income, level of family support, and the role of agricultural extension workers simultaneously affect the participation of KWT members in realizing household food security. The level of availability of free time and the level of family support partially have a significant effect on the participation of KWT members in realizing household food security.